Anodal Transcranial Direct Current Stimulation Over the Supplementary Motor Area Improves Anticipatory Postural Adjustments in Older Adults - Nomura, Tomonori; Kirimoto, Hikari (Frontiers in Human Neuroscience, 2018)
We examined the influence of anodal transcranial direct current stimulation (tDCS) over the supplementary motor area (SMA) on anticipatory postural adjustments (APAs) and center of pressure (COP) sway in older adults. The study enrolled 12 healthy older adult volunteers. Subjects received anodal tDCS (2 mA) or sham stimulation over the SMA for 15 min and performed a self-paced rapid upward arm movement task on a force plate before, immediately after, and 15 min after the stimulation condition. APAs were measured as the temporal difference between activation onset in the deltoid anterior (AD) and biceps femoris (BF) muscles. The root mean square area of COP sway, sway path length, medio-lateral mean velocity, and antero-posterior mean velocity of standing posture were also measured before and after the stimulation condition during the task. Anodal tDCS of the SMA extended APAs and decreased COP sway path length immediately after and 15 min after stimulation compared to baseline. These findings suggest that anodal tDCS over the SMA enhanced APA function and improved postural sway during rapid upward arm movement in older adults.